Preterm birth and weight-for-gestational age for risks of autism spectrum disorder and intellectual disability: A nationwide population-based cohort study - Yu-Shan Chang; Li-Wen Chen; Tsung Yu; Sheng-Hsiang Lin; Pao-Lin Kuo (Journal of the Formosan Medical Association, 2023)
Purpose: To evaluate gestational age (GA) and small-for-gestational age (SGA) as continuums and gender on the incidences of autism spectrum disorder (ASD) and co-occurring intellectual disability (ID). Methods: This is a population-based cohort study using the 2004–2008 Taiwan Maternal and Child Health Database. The diagnosis of ASD was determined by International Classification of Diseases, 9th Revision (ICD-9). Generalized estimating equations models were fit to evaluate associations between perinatal variables and ASD. Results: This study included 916,315 individuals. A total of 9474 (1.0%) children were diagnosed with ASD, among whom 1594 (16.8%) had co-occurring ID. Lower GA carried higher odds of ASD with ID (GA < 28 weeks, aOR: 4.26, 95% CI: 2.13, 8.50; GA 28–30 weeks, aOR: 2.80, 95% CI: 1.57, 4.97; GA 31–33 weeks, aOR: 1.63, 95% CI: 1.05, 2.55; GA 34–36 weeks, aOR: 1.39, 95% CI: 1.16, 1.67) and ASD without ID (GA < 28 weeks, aOR:2.05, 95% CI: 1.25, 3.36; GA 28–30 weeks, aOR: 2.02, 95% CI: 1.46, 2.79; GA 31–33 weeks, aOR: 1.42, 95% CI: 1.13, 1.77; GA 34–36 weeks, aOR: 1.18, 95% CI: 1.08, 1.29). Male preterm infants had ASD risks negatively correlated to GA, while ASD risks were significantly increased only among female infants born late preterm. The degree of SGA showed a stepwise increased risk for ASD with and without ID in both male and female infants. Conclusion: Lower GA and the degree of SGA are both associated with ASD susceptibility, either with or without co-occurring ID, and remarkably increased the risk of ID.